Integrative Treatment for Tinnitus Combining Repeated Facial and Auriculotemporal Nerve Blocks With Stimulation of Auditory and Non-auditory Nerves - Sirh, Soo Ji; Sirh, So Woon; Mun, Hah Yong; Sirh, Heon Man (Frontiers in Neuroscience, 2022)
Background Tinnitus is a prevalent condition (>10% of the population) affecting the quality of life of 0.5–3% of the population. Although many treatments have been proposed, most of these lack evidence of efficacy in the treatment of chronic tinnitus. Thus, this study aimed to evaluate an integrative treatment strategy for subacute and chronic tinnitus. Methods This retrospective chart review study included 55 patients (subacute, n = 15; chronic, n = 40) who underwent repeated nerve blocks after stimulation of the trigeminal (V) and facial (VII) nerves to modulate the auditory and non-auditory nervous systems via the vestibulocochlear (VIII) cranial nerve pathways. We used a simplified smiley tinnitus-visual analog scale (T-VAS) with scores ranging from 0 to 10 combining the effect of tinnitus loudness, distress, and quality of life as the outcome measure to evaluate the efficacy of our treatment method. Statistical analyses were performed using SPSS (version 18.0, SPSS Inc., Chicago, IL), one-way analysis of variance, and t-test. Results In more than 87.5% of patients (14/15 subacute, 35/40 chronic), tinnitus disappeared or had significantly reduced by the end of the treatment. The mean T-VAS score reduced significantly from 7.13 to 0.60 in the subacute group and from 7.73 to 1.53 in the chronic group by the end of treatment (p < 0.05). The average number of treatment procedures was 9.8 ± 3.589 (range, 5–15) in the subacute group and 9.775 ± 3.717 (range, 5–18) in the chronic group. Conclusion Our results show that the proposed integrative approach is highly effective in treating subacute and chronic tinnitus and represents a promising therapeutic approach.